Analisis Model Pembelajaran Berbasis Masalah pada Mata Pelajaran IPS Siswa Kelas V SD Nahdlatul Ulama Sleman Yogyakarta - Ratnasari, Nor Indah; Sukati, Sukati; Badriah, Laelatul (Alma Ata University Press, 2025)
The problem-based learning model with material on various kinds of businesses and economic activities in Indonesia has students who have not met the KKM, which is 30% so that there are 70% of students who have not been able to meet the KKM with the KKM standard at SD Nahdlatul Ulama is 70, while the thinking skills and problem-solving skills of students in class V are still low because students pay less attention to the teacher during the learning process. Therefore, it is necessary to improve problem-based learning in learning activities. Learning with a problem-based learning model will require students to learn how to solve a problem in the real world and acquire the necessary knowledge. PBL can improve critical thinking skills, increase initiative in learning or working, foster internal motivation to learn, and can develop interpersonal relationships in group work. This study aims to determine the analysis of problem-based learning models in social studies subjects of Class V students.The research method used is qualitative description. Sample technique used is purposive sampling. The population and research samples were grade V students with a sample of grade V teachers. Data collection techniques used are interviews, observation, documentation. Data analysis techniques using descriptive qualitative: data reduction, data presentation, drawing conclusions.The results of this study indicate that the analysis of problem-based learning models in social studies subjects of Class V Students of Nadlatul Ulama Elementary School Sleman Yogyakarta is carried out through three stages of analysis, namely the first stage of planning analysis; class V teachers together with the principal and vice curriculum make lesson plans with problem-based learning models, make questions, prepare learning materials, learning models, and learning media in the form of Ball Game media and evaluation questions. Second, the implementation stage; the teacher has carried out or implemented the appropriate problem-based learning steps. Third, the evaluation stage; teachers make written questions in groups and oral questions.Keyword: Problem-Based Learning Model, Social Studies Subject, Class V